Hybrid Textile Nanogenerators Based on Cotton-PANI/CNT Composites for Simultaneous Harvesting of Mechanical and Thermal Energy - Navatragulpisit, Suchanat; Saetang, Chanachot; Mohsom, Phitchayaphorn; Sriphan, Saichon; Pakawanit, Phakkhananan; Hajra, Sugato; Kim, Hoe Joon; Ukasi, Sirinya; Vittayakorn, Naratip; Charoonsuk, Thitirat (My University, 2025)
Rapid advancements in wearable electronics (WEs) have accelerated the development of textile-based triboelectric nanogenerators (T-TENGs) as flexible and sustainable power sources. However, one major challenge lies in mitigating the charge loss due to heat generation during repeated mechanical operations. In this work, we demonstrate a hybrid energy-harvesting textile that integrates both triboelectric and thermoelectric functionalities. Cotton (cot-) fabric serves as the triboelectric substrate, coated with a polyaniline/carbon nanotube (PANI/CNT) thermoelectric composite, enabling the simultaneous harvesting of mechanical and thermal energy. The optimized cot-PANI/CNT device exhibits a high Seebeck coefficient (98.5 mV/K), a power factor of ∼9 μW/mK2, and improved electrical conductivity, while maintaining fabric flexibility. The hybrid system achieves an open-circuit voltage (VOC) of ∼40.0 V and a short-circuit current (ISC) of ∼77.3 μA, yielding a maximum output power of ∼272.3 μW (30.3 μW/cm2). The device successfully powers wearable-scale electronics, and mechanistic insights are provided into the synergistic charge generation pathways between the triboelectric and thermoelectric components.
Keywords: carbon nanotube; cotton; energy-harvesting textiles; hybrid nanogenerator; polyaniline; thermoelectric hybrid materials; thermoelectric nanogenerator; triboelectric nanogenerator; wearable electronics